2007
DOI: 10.1002/mds.21503
|View full text |Cite
|
Sign up to set email alerts
|

Striatal delivery of CERE‐120, an AAV2 vector encoding human neurturin, enhances activity of the dopaminergic nigrostriatal system in aged monkeys

Abstract: Neurturin (NTN) is a potent survival factor for midbrain dopaminergic neurons. CERE-120, an adeno-associated virus type 2 (AAV2) vector encoding human NTN (AAV2-NTN), is currently being developed as a potential therapy for Parkinson's disease. This study examined the bioactivity and safety/tolerability of AAV2-NTN in the aged monkey model of nigrostriatal dopamine insufficiency. Aged rhesus monkeys received unilateral injections of AAV2-NTN into the caudate and putamen, with each animal therefore serving as it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
77
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 128 publications
(86 citation statements)
references
References 44 publications
9
77
0
Order By: Relevance
“…A study using the same expression system in 6-OHDA-lesioned adult rats found long-term neurturin expression in the striatum and dose-dependant protective effects on the nigrostriatal dopaminergic neurones for at least ten months [91]. Similar results were found after application of this system in aged monkeys and no adverse effects were recorded in this study after thorough toxicological testing [93]. A further study by this group found that the expression of neurturin using this system could be sustained for a year in rhesus monkeys, as could its therapeutic effects [94].…”
Section: Effects Of Neurturin In Vivosupporting
confidence: 84%
“…A study using the same expression system in 6-OHDA-lesioned adult rats found long-term neurturin expression in the striatum and dose-dependant protective effects on the nigrostriatal dopaminergic neurones for at least ten months [91]. Similar results were found after application of this system in aged monkeys and no adverse effects were recorded in this study after thorough toxicological testing [93]. A further study by this group found that the expression of neurturin using this system could be sustained for a year in rhesus monkeys, as could its therapeutic effects [94].…”
Section: Effects Of Neurturin In Vivosupporting
confidence: 84%
“…An open-label clinical trial testing a neuroprotective strategy with a gene to synthesize neurturin, an analog of glial-derived neurotrophic factor, is currently underway in 12 subjects. 108 This work is based in part on the positive results of gene therapy studies using recombinant adeno-associated virus carrying a gene for neurturin in monkeys previously exposed to MPTP. 109 Other gene therapy strategies have been proposed from preclinical evidence, based on the potentially neuroprotective activity of several biologically generated substances.…”
Section: Discussionmentioning
confidence: 99%
“…[47][48][49][50][51][52][53] Evidence for restoration has also been found in rodents treated with 6-OHDA 52 and in aged monkeys, in which there is an age-related loss of dopaminergic phenotype. 54 In the later studies, an adenoassociated type 2 viral vector that encoded for human NRTN was injected unilaterally into the striatum of the aged rhesus monkeys. [ 18 F]Fluorodopa uptake was increased in the NRTN vector-treated striatum, compared with the uninjected side, at 4 and 8 months.…”
Section: Neurturinmentioning
confidence: 99%
“…Postmortem examination also revealed an increase in tyrosine hydroxylase immunoreactivity in the injected striatum, relative to the uninjected side. 54 A number of other trophic factors have a protective effect on dopamine neurons in vitro and in vivo. These other factors are generally less well characterized, but potentially have clinical implications (Table 2).…”
Section: Neurturinmentioning
confidence: 99%
See 1 more Smart Citation